1997
DOI: 10.1111/j.1467-8624.1997.tb01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Head Start Parents' Beliefs about Their Children's Abilities, Task Values, and Performances on Different Activities

Abstract: As part of larger intervention study designed to facilitate the transition of Head Start children into kindergarten and the early elementary grades, we assessed parents beliefs about former Head start children's abilities and values in several activity domains-academics, sports, and social skills-during the children's kindergarten ten year. Parents' expectations for their children's future also were examined. One hundred and twenty-four parents and 155 children participated; all children had attended Head Star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…In general, these researchers find that minority children and parents highly value school (particularly during the elementary school years) and have high educational aspirations for their children (e.g., Galper, Wigfield, & Seefeldt, 1997;H. W. Stevenson et al, 1990).…”
Section: Racial and Ethnic Group Differences In Achievement Values Anmentioning
confidence: 99%
“…In general, these researchers find that minority children and parents highly value school (particularly during the elementary school years) and have high educational aspirations for their children (e.g., Galper, Wigfield, & Seefeldt, 1997;H. W. Stevenson et al, 1990).…”
Section: Racial and Ethnic Group Differences In Achievement Values Anmentioning
confidence: 99%
“…Some studies have found positive relationships between parent involvement and children's achievement in emergent literacy, reading, and mathematics (Dickinson & DeTemple, 1998;Fagan & Iglesias;Gauvain, Savage, & McCollum, 2000). Additional studies demonstrate positive associations between maternal engagement and children's sense of self-efficacy (Mantzicopoulos, 1997), and parent expectations and children's interest and motivation in school and learning activities (Galper, Wigfield, & Seefeldt, 1997;Morrow & Young, 1997). Conversely, other studies have found no significant relationships between parent involvement and children's achievement (Gauvain et al, 2000;Sheldon, 2002).…”
mentioning
confidence: 90%
“…Parental beliefs have also been shown to be associated with children's mathematical performance: parents who believe in their children's math competencies have children who do wel1 in mathematics (Entwisle & Alexander, 1990;Entwisle & Baker, 1983;Galper et al, 1997;Hess et al, 1984;Huntsinger et al, 1997;Jacobs, 1991). It has also been suggested that the impact of parental beliefs on children's math performance may be mediated by the children's own achievement-related beliefs and behaviors (Eccles, 1993;Jacobs, 1991;Murphey, 1992).…”
mentioning
confidence: 99%
“…Some studies have focused on parental beliefs conceming a particular skill, such as math or reading (Frome & Eccles, 1998;Galper et al, 1997;Parsons et al, 1982;Phillips, 1987), whereas others have investigated more general beliefs concerning children's overall achievement (Alexander & Entwisle, 1988;Hess et al, 1984;Peet, Powell, & O'Donnel, 1997). Only a few studies have investigated both general and skillspecific beliefs (Baker & Entwisle, 1987).…”
mentioning
confidence: 99%